2008
DOI: 10.1016/j.neulet.2008.08.079
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral consequences of cortical adaptation disruption during ontogeny

Abstract: Filtering of redundant or stable inputs is a critical function of all sensory pathways. Normal sensory gating can allow processing resources to be differentially devoted to changing or otherwise biologically significant stimuli. In olfaction, short-term odor habituation is mediated by a metabotropic glutamate receptor (mGluR)-mediated depression of afferent synapses in the piriform cortex. Given the role of early experience in shaping cortical function and anatomy, the present experiments examined the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This cortical adaptation is mediated by pre-synaptic metabotropic receptors (group III) which reduce glutamate release from mitral/tufted cell axons during repetitive stimulation (Best and Wilson, 2004). Pharmacological blockade of mGluRIII receptors within the piriform cortex prevents afferent synaptic depression, cortical odor adaptation, and short-term behavioral habituation (Bell et al, 2008; Best et al, 2005; Yadon and Wilson, 2005). Noradrenergic inputs to piriform cortex can also reduce synaptic depression (Best and Wilson, 2004), potentially via pre-synaptic beta receptors on mitral cell axons.…”
Section: Olfactory Cortex As An Auto-associative Combinatorial Arraymentioning
confidence: 99%
“…This cortical adaptation is mediated by pre-synaptic metabotropic receptors (group III) which reduce glutamate release from mitral/tufted cell axons during repetitive stimulation (Best and Wilson, 2004). Pharmacological blockade of mGluRIII receptors within the piriform cortex prevents afferent synaptic depression, cortical odor adaptation, and short-term behavioral habituation (Bell et al, 2008; Best et al, 2005; Yadon and Wilson, 2005). Noradrenergic inputs to piriform cortex can also reduce synaptic depression (Best and Wilson, 2004), potentially via pre-synaptic beta receptors on mitral cell axons.…”
Section: Olfactory Cortex As An Auto-associative Combinatorial Arraymentioning
confidence: 99%
“…Keuroghlian and Knudsen (2007) have reviewed experimental evidence showing experience-dependent plasticity in the central auditory representations of sound frequency, level and temporal sequence, as well as in the representations of binaural localization cues in both developing and adult animals. The neurodevelopmental aspects to these processes are essential; Bell et al (2008) have demonstrated that that sensory gating disruption during development can have both immediate and long-lasting effects on sensory-guided behavior. The ''deficient sensorimotor gating'' endophenotype, which leads to abnormalities in attention-associated information processes, bears much weight in the eventual staging of etiopathogenesis of disorder conditions ranging from Tourette's syndrome through attention-deficit hyperactivity disorder (ADHD) and Huntington's disease to schizophrenia.…”
Section: Epigenetics and Prepulse Inhibitionmentioning
confidence: 99%
“…Blockade of group III mGluR receptors prevents cortical adaptation odors (Best and Wilson 2004), and reduces short-term habituation of odor-evoked reflexes (Best et al 2005) and odor investigation (Yadon and Wilson 2005;Bell et al 2008;McNamara et al 2008). This short-term habituation is highly odor specific, with minimal cross-adaptation of piriform cortical single-unit responses or cross-habituation of behavioral responses to similar odors, including between mixtures and their components (Wilson 2000;Cleland et al 2002).…”
mentioning
confidence: 99%